2010
DOI: 10.2503/jjshs1.79.340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photosynthate Transport and Water Flow to Young Fruit on Fruit Drop via Ethylene Synthesis in Persimmon (Diospyros kaki Thunb.)

Abstract: In this study, we aimed to characterize which factors control ethylene production and fruit drop in persimmon (Diospyros kaki Thunb.). We determined the effects of 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU; a specific photosynthesis inhibitor) and defoliation treatments on the photosynthetic rate, transpiration rate, sap flow, fruit drop, and ethylene evolution. DCMU treatment, which prevented photosynthate transport but allowed water flow, promoted fruit drop by 67% 10 days after treatment. Defoliation tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It was reported that ACC treatments, combined or not with sucrose, always increase ethylene production; in contrast, aminoethoxyvinylglycine (AVG) and sucrose reduce the ethylene and ACC. Moreover, branch girdling treatment increases the carbohydrate content and decreases ethylene production, finally decreasing abscission rates (Iglesias et al, 2006;Sun et al, 2010). Finally, a reduction in abscission rate is preceded by elevated concentrations of hexose and starch, but also GAs, in developing ovaries and fruitlets in Satsuma mandarin, suggesting that carbohydrates and GA levels determine fruit set (Mahouachi et al, 2009).…”
Section: Interaction Between Carbohydrates and Hormonesmentioning
confidence: 94%
“…It was reported that ACC treatments, combined or not with sucrose, always increase ethylene production; in contrast, aminoethoxyvinylglycine (AVG) and sucrose reduce the ethylene and ACC. Moreover, branch girdling treatment increases the carbohydrate content and decreases ethylene production, finally decreasing abscission rates (Iglesias et al, 2006;Sun et al, 2010). Finally, a reduction in abscission rate is preceded by elevated concentrations of hexose and starch, but also GAs, in developing ovaries and fruitlets in Satsuma mandarin, suggesting that carbohydrates and GA levels determine fruit set (Mahouachi et al, 2009).…”
Section: Interaction Between Carbohydrates and Hormonesmentioning
confidence: 94%